The Relationship Between Information System Success Factors and the Use of the JKN Mobile Application in the Dungingi Community Health Center Work Area of Gorontalo City - Farti I. Hurudji; Herlina Jusuf; Putri Ayuningtias Mahdang (Universitas Muhammadiyah Palu, 2026)
The Mobile JKN application is an innovation of BPJS Kesehatan digital services that aims to make it easier for participants to access services independently. The success of the implementation of information systems such as Mobile JKN can be analyzed using the DeLone and McLean models which assess six main aspects, namely system quality, information quality, service quality, usage, user satisfaction, and net benefits. The use of the Mobile JKN application in the work area of the Dungingi Health Center is still relatively low, so it is necessary to analyze factors related to its utilization. This study aims to analyze the relationship between the success factor of the information system and the use of the Mobile JKN application in the working area of the Dungingi Health Center, Gorontalo City. This study uses a cross-sectional design with a quantitative approach. The research population is 336 active users of the Mobile JKN application registered at the FKTP Dungingi Health Center, with a sample of 183 respondents selected using purposive sampling techniques. Data analysis was carried out using the Spearman Rank test. The results showed that system quality (p=0.001), information quality (p=0.003), service quality (p=0.000), usage (p=0.001), user satisfaction (p=0.001), and net benefits (p=0.000) had a significant relationship with the use of Mobile JKN applications (p>0.005). Overall, the success factor of the information system was significantly related to the use of the Mobile JKN application with a relationship strength of r=0.407, which was included in the sufficient category based on the correlation value criteria. BPJS Kesehatan and Dungingi Health Center are advised to improve socialization, mentoring, and user understanding so that the use of all features of the Mobile JKN application can be more optimal.